Strongly Directing Substituents in the Radical Arylation of Substituted Benzenes - Hofmann, Josefa; Clark, Timothy; Heinrich, Markus (Journal of Organic Chemistry, 2016)
Although general interest in radical arylation reactions has grown rapidly in recent years, poor regioselectivities and the need to use a large excess of the radical-accepting arene have hindered their application to substituted benzenes. We now describe experimental and computational investigations into the substituent effects that lead to regioselective addition based on the recent discovery of anilines as outstanding substrates for radical arylations.